Polarized microscope assisted study of collagen fibres in Oral Submucous Fibrosis and their clinicopathologic correlation: An in-vitro study - Ameena Singh; Sukumar Singh; Susmita Saxena; Sanjeev Kumar; Akanksha Banga; Nitin Purohit (Elsevier, 2018)
Background: The present study was aimed to evaluate and analyze orientation and birefringence pattern of collagen fibers histopathologically in different grades of OSMF using the special stain (Picrosirius red) under polarizing microscope and relate these factors with the severity of OSMF. Materials and Method: 45 confirmed cases of OSMF were taken from the archives. The selection of clinical cases was done according to classification by J.N Khanna and Andrade (1999). These cases were correlated histopathologically as per the criteria given by Pindborg J.J and Sirsat S.M (1966). The sections were stained with H & E and Picrosirius red stains and assessment was done accordingly. 10 cases of normal mucosa were taken as control. Results: In clinical grade I, 60% of the cases showed histopathological grade II, while 53.4% cases in clinical grade II correlated with histopathological grade III and 33.4% of clinical grade III cases showed histopathological grade IV. Upon application of Fisher's exact test a significant P value <.01 was obtained suggesting no statistical significant correlation between these two parameters. However, the orientation pattern revealed a parallel orientation as OSMF advanced. Also as the severity of the disease increased, there was a gradual shift from green- greenish yellow colour of the fibres and a shift to orange red-red colour. Conclusion: Upon correlation of clinical grades with histopathological grades, no statistically significant difference was found. Birefringence pattern of collagen revealed similar findings as other studies in case of clinical grades but histopathological grades showed a contrast finding.